Pembuatan Virtual Tour pada Situs Sejarah Indonesia Menggunakan Crowdsourcing Foto Digital untuk Mempromosikan Situs Sejarah Nusantara - , (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2016)
Abstract — Promotion of the site's history is one of the important factors for the preservation of the archipelago history. The barrier faced to do is that site promotional media nusantara history which does not draw as well as the expensivecost of publication on media advertising. One of methods that can be used is by utilizing digital photos or digital video taken on historical sites and combines them to form a network of relationships between the photos. User can navigate to look around the history site so it can be used as media promotion. The method used for the incorporation of digital photographs or digital video is a method of bundle adjustment and auto camera calibration. Bundle adjustment is a method used to predict the position of the camera relative to the other cameras, while the auto calibration method of camera was used to predict the intrinsic and extrinsic parameters of digital camera used. By using both of these methods and software for web-based navigation, can be used as media promotion of the history of the archipelago which is interesting, easy, and covering the whole of the history section of the site.